Analisis Penggunaan Aplikasi Deutsch Hören Dalam Meningkatkan Keterampilan Menyimak Bahasa Jerman Mahasiswa - Butar, Nova Ria Butar; Sari, Risnovitas (AR-RUMMAN: Journal of Education and Learning Evaluation, 2025)
This study examines the effectiveness of the Deutsch Hören application in improving German listening skills among students through a literature review. Listening skills are one of the basic competencies in foreign language learning that often pose a challenge for Indonesian students studying German. With the development of digital technology, mobile learning applications such as Deutsch Hören have emerged as an innovative solution to overcome this problem. The research method used is a literature study that analyzes scientific articles relevant to this research. The results of the analysis show that the Deutsch Hören application has a significant positive impact on improving students' listening skills through interactive features, authentic audio material, and an adaptive exercise system. This application has been proven effective in improving listening comprehension, sound discrimination skills, and German spoken text comprehension. In addition, the use of this application also increases student motivation and engagement in the learning process. This study recommends the integration of the Deutsch Hören application into the German language learning curriculum in higher education as a supporting medium that can complement conventional learning methods..